Quality control in Mediterranean fresh food export products - Briz J.; García M.; De Felipe I.; Poole N. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
The paper analyses food safety and quality control in Mediterranean fresh food export products to EU. We focus the analysis on Spain, as one of the leader export countries in fresh agricultural produces, identifying some of the main activities in the supply chain. A comparative analysis was conducted with Tunisia and Turkey, where fieldwork was carried out the citrus and tomato sectors, showing the main results. The study focuses attention on the identification of key no-compliance areas in food safety and quality, through benchmarking and traceability.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)